Patient compliance with braces vs. Invisalign®: a secondary data analysis from a randomized clinical trial - Graziela Hernandes VOLPATO; Paula Vanessa Pedron OLTRAMARI; Renata Rodrigues de ALMEIDA-PEDRIN; Thais Maria Freire FERNANDES; Marcio Rodrigues de ALMEIDA; Gabriela UTRAGO; João POIANI; Ana Cláudia de Castro Ferreira CONTI (Journal of Applied Oral Science)
Abstract The success of orthodontic treatment depends on several factors that may influence the desired outcome, such as patient motivation and cooperation. Objective: This study compared patient compliance during the first year of orthodontic treatment using aligners and conventional fixed appliances. Methodology: The sample included 39 participants (22.1±4.62 years, 25 males, 14 females) randomized into two groups: orthodontic aligners (OA, 20 patients, 23.7±5.6 years, 12 males, 8 females) and fixed appliances (FA, 19 patients, 20.5±4.5 years, 12 males, 7 females). Patient compliance was measured using the Orthodontic Patient Cooperation Scale (OPCS) composed of 10 questions related to attitudes and attendance of patients in relation to treatment. The questionnaire was applied at three different points: at 3 months (T1), at 6 months (T2), and at 12 months (T3) of treatment. The psychosocial profile of the patients was assessed using the anxiety (IDATE) and stress (PSS-14) questionnaires. Both groups were comparable in age, gender and psychosocial profile. Compliance comparisons between groups at T1, T2 and T3, as well as between genders, were performed using the Mann-Whitney test. Comparison between T1, T2 and T3 were performed using the Friedman test. The correlation between age and compliance scores was assessed using the Spearman's correlation coefficient. The psychosocial profile was analyzed using the Independent t-test. All tests considered p<0.05. Results: The type of appliance (OA or FA) and the time of assessment did not significantly influence patient compliance. The age and gender of patients were not correlated with their degree of compliance. Patient compliance was similar in the first 12 months of treatment, regardless of the protocol used, the patient's gender and age. Conclusions: The level of patient compliance with orthodontic treatment was not influenced by the type of appliance (conventional fixed appliances or aligners), nor by the patient's age or gender.